Cultural and linguistic policy abroad : the Italian experience - Totaro-Genevois, Mariella, 1937- (Multilingual Matters S., 2005)
This book investigates Italian foreign cultural policy from the 1947 Constitution to the present. How has Italy conveyed its language and culture to the outside world? Where does the Italian experience fit into a wider international context? Finally, what can be learned from the answers to such questions in relation to the Italian experience in Australia?